Penyuluhan Kepada Karyawati Toko Nadia Collection Tentang Pentingnya Manajamen Pemasaran Digital - Fitra, Jecky; Febliansa, Muhammad Rahman (Universitas Dehasen Bengkulu, 2024)
Nadia Collection Shop is a shop that operates in the field of sales of school children's uniforms, with the best quality. The sales area of the Nadia Collection Shop only serves the Bengkulu city area, with sales techniques displayed at the outlet in the shop. Sales using this technique have not met the target because the sellers are only waiting for sales transactions to occur in shops or outlets so not many schools have ordered. With digital management counseling, it is hoped that employees will be able to promote products widely and make sales easier. This displays product details in detail and produces information on the products being sold. Digital management is a sales system that provides information from several processes including advertising-based sales on social media.